Variations in knowledge, awareness and treatment of hypertension and stroke risk by country income level. Issue 4 (14th December 2020) - O' Donnell, Martin; Hankey, Graeme J; Rangarajan, Sumathy; Chin, Siu Lim; Rao-Melacini, Purnima; Ferguson, John; Xavier, Denis; Lisheng, Liu; Zhang, Hongye; Pais, Prem; Lopez-Jaramillo, Patricio; Damasceno, Albertino; et al.
Abstract : Objective: Hypertension is the most important modifiable risk factor for stroke globally. We hypothesised that country-income level variations in knowledge, detection and treatment of hypertension may contribute to variations in the association of blood pressure with stroke. Methods: We undertook a standardised case-control study in 32 countries (INTERSTROKE). Cases were patients with acute first stroke (n=13 462) who were matched by age, sex and site to controls (n=13 483). We evaluated the associations of knowledge, awareness and treatment of hypertension with risk of stroke and its subtypes and whether this varied by gross national income (GNI) of country. We estimated OR and population attributable risk (PAR) associated with treated and untreated hypertension. Results: Hypertension was associated with a graded increase in OR by reducing GNI, ranging from OR 1.92 (99% CI 1.48 to 2.49) to OR 3.27 (2.72 to 3.93) for highest to lowest country-level GNI (p-heterogeneity<0.0001). Untreated hypertension was associated with a higher OR for stroke (OR 5.25; 4.53 to 6.10) than treated hypertension (OR 2.60; 2.32 to 2.91) and younger age of first stroke (61.4 vs 65.4 years; p<0.01). Untreated hypertension was associated with a greater risk of intracerebral haemorrhage (OR 6.95; 5.61 to 8.60) than ischaemic stroke (OR 4.76; 3.99 to 5.68). The PAR associated with untreated hypertension was higher in lower-income regions, PAR 36.3%, 26.3%, 19.8% to 10.4% by increasing GNI of countries. Lifetime non-measurement of blood pressure was associated with stroke (OR 1.80; 1.32 to 2.46). Conclusions: Deficits in knowledge, detection and treatment of hypertension contribute to higher risk of stroke, younger age of onset and larger proportion of intracerebral haemorrhage in lower-income countries.